Application of Multitrack Mixing in Dangdut Music: An Analysis of Jujuk Eksa Technique - Hutomo Ardi, Dony; Mochammad Usman Wafa (Universitas Negeri Semarang, 2024)
This study aims to describe the analysis of Jujuk Eksa’s techniques in applying multitrack mixing to dangdut music, emphasizing the genre's distinctive use of the kendang drum. Jujuk Eksa is a sound engineer who specializes in music production across various genres, including dangdut, keroncong, congdut, and Javanese langgam. His extensive experience includes collaborations with renowned national musicians such as Didi Kempot, Nurhana, and Soleh Akbar. This research employs a qualitative descriptive method, integrating a musicological approach to examine dangdut music and a technological approach to analyze mixing techniques. The study involves in-depth interviews with Jujuk Eksa, direct observation of the mixing process, and documentation analysis of mixing data. The findings reveal three key aspects: (1) Preparation, which includes ensuring data feasibility, determining the appropriate formula, and considering musical arrangements; (2) Treatment, comprising essential mixing procedures such as setting levels, equalization, dynamic processing, reverb effects, harmonic enhancement, and pre-mastering, which encompasses mixdown and normalization as the finalization process; and (3) Mixing Focus, highlighting the critical role of leveling and panning in the multitrack mixing process of dangdut music. Overall, this research underscores the significance of precise mixing techniques in preserving the unique characteristics of dangdut music production.